2006
DOI: 10.1053/j.gastro.2006.08.012
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Is Important for Chylomicron Formation and Secretion and May Mediate Cholesterol Uptake in the Proximal Intestine

Abstract: Background & Aims-Studies are aimed to determine the role of CD36 in intestinal lipid absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
166
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 34 publications
9
166
1
3
Order By: Relevance
“…CD36 is expressed in epithelial cells of the small intestine along the gastro-colic and crypt-to-villus axes in a pattern paralleling that of other proteins implicated in FA uptake such as intestinal and liver FA-binding proteins (5)(6)(7). In addition, we have shown that CD36 is important for chylomicron production and acute FA uptake in the proximal intestine (8,9). * This work was supported, in whole or in part, by National Institutes of Health Grants DK060022 (to N. A.…”
supporting
confidence: 54%
“…CD36 is expressed in epithelial cells of the small intestine along the gastro-colic and crypt-to-villus axes in a pattern paralleling that of other proteins implicated in FA uptake such as intestinal and liver FA-binding proteins (5)(6)(7). In addition, we have shown that CD36 is important for chylomicron production and acute FA uptake in the proximal intestine (8,9). * This work was supported, in whole or in part, by National Institutes of Health Grants DK060022 (to N. A.…”
supporting
confidence: 54%
“…Chylomicron size is highly dependent on expression levels of a few LBPs and apolipoproteins. For instance, FAT/CD36 knockout mice secrete smaller chylomicrons than wild-type mice (30), and the induction of intestinal apoA-IV has been reported to lead to larger particles (27,31). According to these data, the fat-mediated increase of genes encoding FAT/CD36 and apoA-IV might produce large chylomicrons rapidly hydrolyzed by LPL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, overexpression of CD36 in COS-7 cells has been shown to enhance cholesterol uptake from micellar substrates (184). In another study, CD36-null mice showed a significant reduction in cholesterol transport from the intestinal lumen to the lymphatic system (133). Decreased cholesterol uptake has been shown in brush-border membrane vesicles prepared from the proximal (but not distal) intestine of SR-BI-KO mice (184) and in brush-border membrane vesicles and Caco-2 cells preincubated with antibodies to SR-BI (71).…”
Section: Cholesterolmentioning
confidence: 99%